Etnomusikologi Indonesia: Menyoal Representasi, Menemukan Relevansi - Setiyono, Budi (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2022)
The discipline of Ethnomusicology in Indonesia still has problems related to issues of representation, relevance and contribution to benefit. This paper will discuss how efforts are being made to realize the discipline of Indonesian Ethnomusicology and offer more relevant paths. The discussion is qualitatively based on a general review of the historical setting of the emergence of representation issues in the Ethnomusicology discipline, considering the urgency of the representation issue in the context of Ethnomusicology in Indonesia and trying to read the Indonesian context to be able to offer a more relevant style of discipline. Questioning representation is an important matter in the discipline of Ethnomusicology in Indonesia, but there is work that needs to be done more hastily. Designing scientific disciplines that can help answer socio-political and cultural issues, such as issues of tolerance, radicalism, conflicts between groups, issues of ecology, economy and culture itself will be more able to make ethnomusicology more beneficial.